Psychosocial factors associated with lower extremity reinjury risk in soccer players: contribution of self-confidence and reinjury anxiety - Naderi, A.; Rahimi, M.; Zarghami, S. Y.; Tranaeus, U.; Calmeiro, L. (Journal of Athletic Training, 2024)
Context Despite the availability of specialized assessment tools, psychological readiness is usually not considered when deciding to return to sport (RTS) after sport injury. Reinjury anxiety, self-confidence, and functional attention may be associated with sport reinjury, making it important to evaluate these factors before RTS.